IMPLIMENTATION OF INTELLIGENT CAP WITH DROWSY DETEC TION AND VEHICLE MONITORING - Sushma Telrandhe,; Darshana Nimje,; Rohit Nitnaware, (International Journal of Innovations in Engineering Research and Technology, 2021)
Drowsiness”, a state which is often seen in drivers now-a-dayshas become a serious issue in roadmishaps. Driver fatigue resulting from sleep deprivation or sleep disorders is an important factor in theincreasing number of accidents. The development of technology for preventing drowsiness at the wheel isa major challenge in the field of accident avoidance system. .Sleepy drivers often do not take correctaction prior to a collision.